Synthesis of Hexa-peri-hexabenzocoronenes for batteries - Bay, Ming Chuen (2012)
Self-assembled nanostructures such as Hexa-peri-hexabenzocoronenes (HBCs) have received increased attention due to their potential for organic and supramolecular electronics. HBC has a highly extended pi-conjugated system which allows flexible side chains of polycyclic aromatic hydrocarbons to be incorporated into an aromatic core. This causes incompatible segments to be phase separated from one another and enhance ordering of aromatic units responsible for charge carrier transport. Recent studies on HBC derivatives have shown that they readily self-assemble affording discotic liquid crystals and nanofibers.